Adapting the facial action coding system for chimpanzees (Pan troglodytes) to bonobos (Pan paniscus): the ChimpFACS extension for bonobos - Catia Correia-Caeiro; Paul Henrik Kuchenbuch; Linda S. Oña; Franziska Wegdell; Maël Leroux; André Schuele; Jared Taglialatela; Simon Townsend; Martin Surbeck; Bridget M. Waller; Katja Liebal (PeerJ)
The Facial Action Coding System (FACS) is a widely recognised coding scheme for analysing human facial behaviour, providing an objective method to quantify discrete movements associated with facial muscles, known as Action Units (AUs), and reducing subjective bias. FACS has been adapted for nine other taxa, including apes, macaques, and domestic animals, but not yet bonobos. To carry out cross species studies of facial behaviours within and beyond apes, it is essential to include bonobos. Hence, we aimed at adapting FACS for bonobos. We followed a similar methodology as in previous FACS adaptations: first, we examined the facial muscular plan of bonobos from previously published dissections. Given the similarity between bonobo and chimpanzee musculature, we tested if ChimpFACS for chimpanzees could be applied to bonobos. Second, we used ChimpFACS to analyse spontaneous facial behaviour in bonobos through videos recorded in various contexts. Third, we noted any differences in appearance changes between the AUs included in ChimpFACS and the AUs observed in bonobos. Our findings showed that bonobos exhibit all the facial movements observed in chimpanzees, and thus ChimpFACS can reliably be applied to bonobos. Bonobos presented a diverse repertoire of 28 facial movements (22 AUs, three Action Descriptors, and three Ear Action Descriptors). Although the range of facial movement is lower than in humans, bonobo’s potential for facial movement is comparable to that of chimpanzees, underscoring the significance of this behaviour modality during social interactions for both species. The ChimpFACS Extension for bonobos is an objective coding scheme for measuring facial movements in bonobos, designed to be used in conjunction with ChimpFACS. This coding scheme extension will allow us to better understand bonobos’ behaviour and communication, with practical applications for assessing their welfare, particularly in human care. It also provides a framework for comparing primate species, contributing to insights into the origin and evolution of facial emotion and communication.